2020
DOI: 10.1002/dneu.22795
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ash1l in Tourette syndrome and other neurodevelopmental disorders

Abstract: Ash1l potentially contributes to neurodevelopmental diseases. Although specific Ash1l mutations are rare, they have led to informative studies in animal models that may bring therapeutic advances. Ash1l is highly expressed in the brain and correlates with the neuropathology of Tourette syndrome (TS), autism spectrum disorder, and intellectual disability during development, implicating shared epigenetic factors and overlapping neuropathological mechanisms. Functional convergence of Ash1l generated several signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 105 publications
0
11
0
Order By: Relevance
“…1F ), compared to control transfected neurons, with no significant differences between the different ASH1L shRNA transfected neurons. In published mouse models of ASH1L deficiency, the reduction in ASH1L levels in heterozygous animals is between 50 to 60% 38 , 41 , 42 . While defects in neuronal excitability were reported in one study 42 to date, no major brain anatomical phenotypes have been reported in published studies of heterozygous animals 38 , 41 , 42 .…”
Section: Resultsmentioning
confidence: 99%
“…1F ), compared to control transfected neurons, with no significant differences between the different ASH1L shRNA transfected neurons. In published mouse models of ASH1L deficiency, the reduction in ASH1L levels in heterozygous animals is between 50 to 60% 38 , 41 , 42 . While defects in neuronal excitability were reported in one study 42 to date, no major brain anatomical phenotypes have been reported in published studies of heterozygous animals 38 , 41 , 42 .…”
Section: Resultsmentioning
confidence: 99%
“…2017 ). A review by Zhang and colleagues highlighted the possible role of variants in ASH1 Like Histone Lysine Methyltransferase ( ASH1L) in the etiology of psychiatric disorders including TS, autism spectrum disorders and intellectual disability ( Zhang et al . 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Since mutations in ASH1L have previously been associated with several neurological disorders, including ASD [15,17], Attention-deficit/hyperactivity disorder [46], and Tourette syndrome [47,48], we tested the viability of our mutant ASH1L ESCs for neuronal induction. Our lab routinely uses a dual-SMAD inhibition protocol that leads to the generation of excitatory cortical neurons [29].…”
Section: Resultsmentioning
confidence: 99%